1987
DOI: 10.1002/ijc.2910400518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a single injection of anti‐asialo GM1 serum on natural cytotoxicity and the growth of a regressive colonic tumor in syngeneic rats

Abstract: The REGb tumor cell line is a cloned variant of the DHD-K12 cell line, established from a colon carcinoma chemically induced in the rat. Unlike the parent DHD-K12 cell line, or other clones, which give progressive tumors when inoculated to the syngeneic rat, REGb cells produce tumors which regress in 3 to 5 weeks and never cause metastasis. In order to explore the role of natural killer (NK) cells in REGb tumor regression, each rat was given one injection of anti-asialoGM1 (anti-asGM1) serum, a known inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It has been reported previously that NK activity is strikingly eliminated when anti-asialo GM1 is injected, and that the eliminated activity can be maintained by repeated injections at 3-day intervals (12), although it is still unclear whether such an increase in ACF is directly due to the inhibition of NK cells. The dose of anti-asialo GM1 used in this study was sufficient to induce the total elimination of the high-density fraction of large granular lymphocytes in the liver of Wistar rats (13), and to inhibit cytotoxicity of the peripheral blood lymphocytes for two weeks after injection (14). Although this dose of anti-asialo GM1 may not completely inhibit NK activity in the large bowel, the number of ACF in the distal large bowel increased significantly (Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…It has been reported previously that NK activity is strikingly eliminated when anti-asialo GM1 is injected, and that the eliminated activity can be maintained by repeated injections at 3-day intervals (12), although it is still unclear whether such an increase in ACF is directly due to the inhibition of NK cells. The dose of anti-asialo GM1 used in this study was sufficient to induce the total elimination of the high-density fraction of large granular lymphocytes in the liver of Wistar rats (13), and to inhibit cytotoxicity of the peripheral blood lymphocytes for two weeks after injection (14). Although this dose of anti-asialo GM1 may not completely inhibit NK activity in the large bowel, the number of ACF in the distal large bowel increased significantly (Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…These observations suggested involvement of NCMC in host resistance against tumor growth in vivo. In our model, the antitumoral role of naturally cytotoxic anti-asGMl-sensitive cells was assessed in vitro [28] as well as in vivo [32]. Nevertheless the exact nature of the effector cells active against REGb cells remained to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Effector cells were, at least in the majority, anti-asGM1 sensitive [28]. Moreover, REGb cells produced progressive and even metastatic tumors in rats treated by anti-asGM1 antibody prior to the injection of tumor cells [32]. Thus BDIX naturally cytotoxic antiasGMl-sensitive cells appeared involved in mechanisms leading to the regression of REGb tumors but it remained to exactly define their nature.…”
Section: Introductionmentioning
confidence: 95%
“…3,12,19 Previous studies have demonstrated the efficacy of two methods of residual immune system deactivation: whole body irradiation 2,15,[27][28][29][30] and injection of asialo-GM1 antibody. 24,28,31,32 Some research has suggested a combined positive effect with both therapies, 30 but this result has been disputed. 18 Our results demonstrate that the use of radiation alone or with antibody to asialo-GM1 enhanced the ability of SCID mice to support selected leukemia and lymphoma cell growth.…”
Section: Discussionmentioning
confidence: 99%